2010
DOI: 10.1007/s00330-010-1974-5
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of benign and malignant uterine corpus tumors by using proton MR spectroscopy at 3T: preliminary study

Abstract: Proton MR spectroscopy with quantitative evaluation of tCho concentration can provide helpful information in distinguishing benign and malignant uterine corpus tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…McLean et al and Takeuchi et al applied LCModel to quantify the choline concentration in evaluating ovarian tumours and uterine corpus tumours, respectively [7,13]. They found that MR spectroscopy could be measured at 3T with acceptable spectral quality and good signal-to-noise ratio for quantitative analysis of metabolites [7,13]. In our study MR spectroscopic data obtained at 3T were also good for the qualitative and quantitative evaluation.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…McLean et al and Takeuchi et al applied LCModel to quantify the choline concentration in evaluating ovarian tumours and uterine corpus tumours, respectively [7,13]. They found that MR spectroscopy could be measured at 3T with acceptable spectral quality and good signal-to-noise ratio for quantitative analysis of metabolites [7,13]. In our study MR spectroscopic data obtained at 3T were also good for the qualitative and quantitative evaluation.…”
Section: Discussionsupporting
confidence: 65%
“…In several studies LCModel has been applied for the quantification of metabolites in gynaecologic tumours [7,13,26,27]. McLean et al and Takeuchi et al applied LCModel to quantify the choline concentration in evaluating ovarian tumours and uterine corpus tumours, respectively [7,13]. They found that MR spectroscopy could be measured at 3T with acceptable spectral quality and good signal-to-noise ratio for quantitative analysis of metabolites [7,13].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, there are some contradictory data. In studies regarding the uterine tumors, Okada et al (59) and Celik et al (60) found that choline was present in benign and malignant lesions, while Takeuchi et al (61) reported that malignant lesions have higher levels of choline, and a cutoff of 7 mmol might distinguish between them with 83% sensitivity and 93% specificity. Lipid peaks also showed promising results for distinguishing uterine sarcomas from benign leiomyomas (62).…”
Section: Genitourinary Tumors (Excluding Prostate)mentioning
confidence: 99%